2013
DOI: 10.1186/1471-2164-14-352
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRNAs associated with sexual maturity in chicken ovary by Illumina small RNA deep sequencing

Abstract: BackgroundMicroRNAs have been suggested to play important roles in the regulation of gene expression in various biological processes. To investigate the function of miRNAs in chicken ovarian development and folliculogenesis, two small RNA libraries constructed from sexually mature (162-day old) and immature (42-day old) ovary tissues of Single Comb White Leghorn chicken were sequenced using Illumina small RNA deep sequencing.ResultsIn the present study, 14,545,100 and 14,774,864 clean reads were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
68
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 61 publications
16
68
0
2
Order By: Relevance
“…Hens were killed by cervical dislocation, and the ovaries were collected immediately. The whole ovary was harvested for RNA sequencing [16] or protein extraction for comparing ovarian MMP expression between prepubertal and mature hens. Different follicles, including small white follicles and F4, F3, F2, F1, POF1, and POF2 follicles, were manually dissected out for RNA or protein extractions for analyzing MMP expression in the different follicles.…”
Section: Animals and Tissue Harvestmentioning
confidence: 99%
“…Hens were killed by cervical dislocation, and the ovaries were collected immediately. The whole ovary was harvested for RNA sequencing [16] or protein extraction for comparing ovarian MMP expression between prepubertal and mature hens. Different follicles, including small white follicles and F4, F3, F2, F1, POF1, and POF2 follicles, were manually dissected out for RNA or protein extractions for analyzing MMP expression in the different follicles.…”
Section: Animals and Tissue Harvestmentioning
confidence: 99%
“…No fewer than 93 MIRs (of as yet unknown function) are differentially expressed within the ovary of immature pullets compared to sexually mature hens, and a subpopulation of these continue to be expressed at different levels during subsequent follicular growth and development (30). The initial, slow growth of follicles measuring 60-100 µm in diameter occurs over several months via the uptake of a lipoprotein-rich yolk by the oocyte, concurrent with the expansion of the single layer of granulosal cells.…”
Section: Follicular Development At Sexual Maturationmentioning
confidence: 99%
“…The expression difference of gga-miR-1a and gga-miR-21 in immature and mature chicken ovaries and different sized follicles suggested that they conducted an important effect on chicken follicular growth or ovulation mechanism [24]. A related research promulgated that miRNA-133a and miR-1a were muscle-related, whereas miR-122 was adipose-related miRNA in chickens [25].…”
Section: Discussionmentioning
confidence: 97%